The Economic Value of Urban Forest In Jakarta (Case Study Srengseng Urban Forest West Jakarta) - Saqinah Nur Rahmawati; Dudung Darusman; Rachmad Hermawan; Ricky Avenzora (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
The city of Jakarta has many environmental problems, among others it requires the existence of urban forests could ameliorate micro climate. Air temperature and humidity as part of the microclimate element affect the level of comfort that will ultimately affect quality the society. It is necessary to quantitatively calculate the economic value of the urban forests so that its existence is considered need for the city. This study firstly aims to analyze the perception of visitors and communities on the benefits of urban forests, secondly to analyze the microclimate of urban forest, and thirdly to estimate the economic value of urban forest in Jakarta. The research was conducted in Srengseng Urban Forest, West Jakarta. The research data was collected during November 2016-February 2017. The result showed that visitor and comunities perception of the benefit of urban forests are positive. Urban forests are able to ameliorate microclimate which is characterized by air temperatures in urban forest is lower than outside, and air humidity in urban forests is higher than outside so that the Temperature Humadity index (THI) value inside urban forests are lower than outside. Although quantitatively through the urban forest THI value it falls into the uncomfortable category (THI>28) but qualitatively by perception visitors and communities that urban forests is comfort. Total WTPs from urban forest visitors and communities around the urban forest were Rp 743,743,040/year per hectare with periode contribution per visit and Rp 264,311,067year per hectare with periode contribution per month. Keywords: economic value, Jakarta City, urban forest, willingness to pay